The Improbable Conquest : Sixteenth-Century Letters from the Río de la Plata - Garrett, Victoria L. (Victoria Lynn), 1981-; Garrett, Victoria L. (Victoria Lynn), 1981-; García Loaeza, Pablo, 1972-; García Loaeza, Pablo, 1972- (Book collections on Project MUSE., 2015)
"A translation of letters written by settlers in the Río de la Plata region of South America during the Spanish conquest in the sixteenth century"--Provided by publisher.